Infection Rate of Theileriosis in Sheep Population in District Kohat - Majid, Hafiz Abdul; Shah, Shaheed Ullah; Abdur Raziq; Muhammad Shoaib; Muhammad Mujtaba; Khan, Hamayun; Ahmad, Israr; Hafeez Ur Rehman; Raza, Hafiz Ahsan; Qamar Ullah (Indus Journal of Bioscience Research, 2024)
To Ovine theileriosis, a tick-borne disease caused by Theileria species poses significant economic and health burdens on livestock production worldwide. This cross-sectional study investigated the prevalence and risk factors associated with Theileria infection in sheep populations in District Kohat, Pakistan. A total of 200 blood samples were collected from sheep across four tehsils and examined microscopically. The overall prevalence of theileriosis was 43.5% (95% CI: 36.4-50.6), with significant variations across tehsils (28.9%-49.1%). Multivariate analysis revealed significant associations between Theileria infection and age (p < 0.05), body condition score (p < 0.05), sex (p < 0.05), and season (p < 0.05). Younger sheep (<1 year), males, and those with poor body condition scores were identified as high-risk groups. Seasonal analysis showed a higher prevalence during summer (60%, p < 0.01). The high prevalence of theileriosis in District Kohat highlights the need for targeted interventions and preventive measures to mitigate its impact on sheep production. Improved animal husbandry practices, tick control strategies, and vaccination programs could reduce the disease burden. The study’s findings contributed to the ovine theileriosis epidemiology in Pakistan and informed evidence-based control measures.